Game Edukatif Strategi Efektif Mengasah Kemampuan Berpikir Kritis Anak Usia Dini - Aviska, Shella (Maliki Interdisciplinary Journal, 2025)
This study examines the role of educational games in enhancing critical thinking skills among early childhood learners. Critical thinking involves the ability to analyze, compare, predict, and solve problems logically skills that are essential to develop from an early age as preparation for 21st-century challenges. Educational games, both digital and tangible forms such as loose parts, provide interactive and enjoyable learning experiences that encourage children to actively construct their own knowledge. The findings indicate that educational games can significantly improve children’s abilities in classification, comparison, and prediction, while also fostering creativity, collaboration, communication, and positive character traits such as discipline, responsibility, and empathy. Therefore, integrating educational games into learning activities serves as an effective strategy to nurture children’s cognitive, social, and emotional skills from an early age.